1998
DOI: 10.1176/ajp.155.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in the Vietnam Generation: Findings From a Nationally Representative Sample of Male Vietnam Veterans

Abstract: Frequent nightmares appear to be virtually specific for PTSD. The nightmare is the domain of sleep disturbance most related to exposure to war zone traumatic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
243
1
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 409 publications
(264 citation statements)
references
References 29 publications
12
243
1
8
Order By: Relevance
“…4 Trauma-related nightmares in PTSD are more severe than non-trauma-related nightmares in terms of increased frequency and association with more frequent awakenings and worse sleep maintenance. 5,6 In the National Comorbidity Survey Replication of American adults, the lifetime prevalence of PTSD was 6.8%. 7 With an increasing number of veterans of military deployments being reintegrated into civilian life, physicians can expect to see more patients with symptoms of PTSD, including nightmares and reduced sleep quality.…”
mentioning
confidence: 99%
“…4 Trauma-related nightmares in PTSD are more severe than non-trauma-related nightmares in terms of increased frequency and association with more frequent awakenings and worse sleep maintenance. 5,6 In the National Comorbidity Survey Replication of American adults, the lifetime prevalence of PTSD was 6.8%. 7 With an increasing number of veterans of military deployments being reintegrated into civilian life, physicians can expect to see more patients with symptoms of PTSD, including nightmares and reduced sleep quality.…”
mentioning
confidence: 99%
“…Several representative studies have reported nightmare incidences of 50-70% in adults suffering from PTSD (Kilpatrick, et al, 1998;Leskin, Woodward, Young, & Sheikh, 2002;Neylan, et al, 1998) results. One large scale study including Kurdish children indicated that trauma exposure was related to more realistic dreams lacking in bizarreness and symbolism (Punamäki, Ali, Ismahil, & Nuutinen, 2005).…”
mentioning
confidence: 99%
“…Several representative studies have reported nightmare incidences of 50-70% in adults suffering from PTSD (Kilpatrick, et al, 1998;Leskin, Woodward, Young, & Sheikh, 2002;Neylan, et al, 1998). Many studies have shown an association between posttraumatic nightmares and indicators of functional impairment, such as psychiatric symptoms, time off work, psychosomatic reactivity, and sleep problems (e.g., Holen, 1990;Neylan et al, 1998).…”
mentioning
confidence: 99%
“…Among those meeting diagnostic criteria for posttraumatic stress disorder (PTSD), the prevalence of insomnia and other sleep difficulties is even greater. An estimated 10-25 % of Veterans deployed to Iraq and Afghanistan have returned with PTSD (Tanielian & Jaycox, 2008), and up to 90 % of these Veterans are likely to endorse difficulty maintaining sleep (Neylan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%